CHEMICAL STABILITY AND ADSORPTION SELECTIVITY ON Cd2+ IONIC IMPRINTED Nannochloropsis sp MATERIAL WITH SILICA MATRIX FROM TETRAETHYL ORTHOSILICATE - Buhani Buhani; Suharso Suharso; Liza Aprilia (Indonesian Journal of Chemistry, 2012)
Chemical stability, reusability, and adsorption selectivity of Cd2+ ionic imprinted Nannochloropsis sp with silica matrix (Cd(II)-IIP) from precursor tetraethyl orthosilicate (TEOS) have been studied through adsorption experiment series with batch method. Nannochloropsis sp (Cd(II)-IIP) material was characterized with an infrared spectrophotometer (IR) to identify the functional groups in this material and identification of metal ion concentration was analyzed with an atomic absorption spectrophotometer (AAS). Chemical stability was determined in solution media of acid, neutral, and base. Adsorption selectivity was obtained with determination of selectivity coefficient (α) of Cd2+ ion toward its ionic pair such as Ag+, Zn2+, Cu2+, and Ni2+ ions. Nannochloropsis sp Cd(II)-IIP material is very stable in acid media and lack stable in base media as well as it can be reused for extraction 4 cycles with adsorption capacity value > 95% using eluent of 0.1 M Na2EDTA. Selectivity of Cd(II)-IIP material upon Cd2+ ion is higher than non imprinted polymer (NIP) and it increases with these orders; Cd2+/Ag+ < Cd2+/Zn2+ < Cd2+/Cu2+ < Cd2+/Ni2+ for each α at metal ionic ratio of 1:1; 0.887; 20.180; 28.053; 33.417, respectively.